PERBANDINGAN PEMBAGIAN WARISAN UNTUK JANDA MENURUT KITAB UNDANG-UNDANG HUKUM PERDATA DAN KOMPILASI HUKUM ISLAM - Riki Budi Aji; Maryati Bachtiar; Dasrol ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Widow as heir there are many similarities and differences in system of Islamic law with Western legal system where people are less aware of the similarities and differences. Inheritance law provisions regarding inheritance for widows there are very significant differences between the provisions of the Civil Code and the laws of Islam. Based on the explanation and the above background, the authors are interested in the discussion raised in a scientific study entitled " THE COMPARISON OF LEGACY SHARING FOR THE WIDOW ACCORDING TO CIVIL LAW AND COMPILATION ISLAMIC LAW"Basically, this research aims to achieve a proper understanding of the problems formulated. More specifically, the purpose of the study can be described as follows: First, to determine the position of widows as heirs in inheritance according to the Civil Code and Islamic Legacy Law. Second, to determine the distribution of inheritance to widows based on the Civil Code and Islamic Legacy Law. Third, to determine similarities and differences in the law about the division of inheritance for widows according to the Civil Code and Islamic Legacy Law.. The conclusion is First, Equation Position Widow as heir based based on the Civil Code and is based on Islamic Legacy Law is the class of the priority to be heir, so it is not obstructed heir heirs other than by virtue. Second, the difference, in the Civil Code Widows who do not have children or descendants heir entitled to the entire inheritance. While in Islamic Inheritance Law Widow heir with his parents and brothers heir. The amount of the legacy of the Civil Code for Widow equated with the legitimate child of the head-by-head. While the magnitude of the inheritance to the widow in Islamic inheritance according Islamic Legacy Law sourced from Al Quran has been determined, the 1/4 or 1/8.